Morphogenesis of urinary bladder of rats in early postnatal period - Khitrik, A. J.; Yevtushenko, V.; Nemyrskyi, V.; Bushman, V.; Necheporenko, A.; Aksamiteva, M.; Хитрик, Аліна Йосипівна; Євтушенко, Валентина Михайлівна; Немирський, В.; Бушман, Вікторія Сергіївна; Нечепоренко, Альона Геннадіївна; Аксамитьєва, Марія Володимирівна (German Science Herald, 2019)
The actual problem of practical medicine is the treatment of diseases of the lower part of the urinary system and about 20% of this pathology accounts for the bladder pathology. The purpose of this research was to study the morphological characteristics of the bladder of rats in the period of early postnatal ontogenesis. A histological survey of the bladders of 40 rats was conducted. Quantitative analysis of the results of the morphometric study was carried out using methods of variation statistics using Excel and STATISTICA. The aim of the study was to determine the average thickness of the lamina propria, the average number of microvessels in the unit of area, the number of lymphocytic cells. During the early stage of postnatal ontogenesis (up to 90th day of life of rats), the following changes in the structure of the bladder were observed: an increase in the thickness of the bladder mucous membrane; an increase of cells of the immunomorphological complex (lymphocytes, macrophages, and lymphocytic cell clusters), changes in theirs quantitative aspect and in the diversity of the cellular composition; an increase in the number of blood vessels in the microcirculatory bed. These changes occurred progressively, with maximum expressiveness on the 30th day of life and subsequent stabilization of indicators. This may be caused by a change in the diet of rats, since from 14th to 21st day there was a transition from dairy to natural nutrition. It is planned to conduct an investigation of the effect of antigenic stimulation on the structure of the wall of the bladder in the future.
Khitrik A. - ORCID 0000-0003-0111-6016, Bushman V. - ORCID 0000-0002-5833-0155, Necheporenko A. - ORCID 0000-0003-0981-3641, Aksamiteva M. - ORCID 0000-0002-8168-1869.
Keywords: postnatal ontogenesis; bladder; lymphocyte; microcirculatory channel